KOMUNIKASI INSTRUKSIONAL PELATIH DALAM MEMBINA SISWA SEPAK BOLA TIGA NAGA FOOTBALL ACADEMY AND SOCCER SCHOOL PEKANBARU - Fajar Kustianto; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Tiga Naga Football Academy and Soccer School Pekanbaru is a football school (SSB). This soccer school has facilities in the form of a residence for students who go to school, a field for soccer practice, a gym and an office. Tiga Naga Trainer is A-AFC and B-AFC certified. Tiga Naga has recorded many achievements and champions. The purpose of this study was to determine the instructional communication of coach in developing football students Tiga Naga Football Academy and Soccer School Pekanbaru which can be seen from methods, messages, media and obstacles during the fostering process used by coaches.This research method uses descriptive qualitative method. The subjects of this study were the owner, manager, coach and students of football students Tiga Naga Football Academy and Soccer School Pekanbaru. While the object of the instructional communication of coach in developing football students Tiga Naga Football Academy and Soccer School Pekanbaru. Data collection techniques used were interviews, observation and documentation. Data analysis techniques using an interactive data analysis model. In achieving data validity in this study, the authors used an extension of participation and triangulation.The results showed that instructional communication by the trainer used programmed instructional methods, simulation methods, training methods, and discussion methods. Instructional communication messages in the form of persuasive messages and informative messages. To support instructional communication so that it runs smoothly, media in training is needed. The media used by the coaches are visual media such as balls, goalposts, strategy boards, cone bowls, cone cones, training marker post, soccer wall, soccer adjustable hurdles, training hurdle, speed agility ladder and audio-visual media that is using video of the results of matches, laptops and infocus. Meanwhile, instructional communication barriers that occur in the form of psychological and physical barriers.Keywords :Instruksional Comunication, coach, soccer school.